Moral authority, men of science, and the Victorian novel - DeWitt, Anne (Cambridge University Press, 2013)
How did Victorian novelists including Eliot, Hardy and Wells respond to contemporary men of science who aligned scientific practice with moral excellence in an endeavor to secure cultural authority for their discipline? Anne DeWitt argues that novelists came to reject this alignment, denying that science held widely accessible moral benefits.